Pemberdayaan Masyarakat Pesisir Terpadu Desa Tapulaga Melalui Konservasi Ekosistem Lestari: Pemberdayaan Masyarakat Pesisir Terpadu Desa Tapulaga Melalui Konservasi Ekosistem Lestari - Halili Adimu; Wellem H Muskita; Wanurgaya Adimu; Hasnia Adimu; Moh Nuh Ibrahim Adimu; Hasan Eldin Adimu; Andi Asmaul Husna Adimu (PUSAKA ABDIMAS, 2025)
This program adopts an integrated, community-based approach, in line with national conservation policies for marine areas and small islands, to support the blue economy and community food security. Key activities include seagrass transplantation, beach cleanups, and fish floss training for housewives, designed with active community participation in mind. The community service activities were conducted from September 13 to October 13, 2025, in Soropia District, Konawe Regency. Through four main programs: seagrass transplantation, beach cleanups, fish floss production, and the installation of warning signs prohibiting fish bombing, this activity successfully raised public awareness of the importance of maintaining marine ecosystems and coastal cleanliness. Furthermore, this program also encouraged the sustainable use of natural resource potential, opened new economic opportunities through processed seafood products, and strengthened the community's sense of responsibility for the environment.